Use of Penn State Particle Separator for the evaluation of total mixed rations typical of Parmigiano Reggiano cheese production area - B. Gandolfi; M. Renzi; A. Quarantelli; L. Tonelli; F. Righi (Italian Journal of Animal Science, 2010)
An observational study was conducted on 18 dairy farms located in the area of Parmigiano Reggiano cheese production with the aim to supply some recommendations regarding the more efficient TMR physical form. The effects of TMR particle size distributions on digestion process and on dairy productivity were investigated. Lower particle size appeared to improve digestion process and resulted in increased DMI, milk yield, and milk casein level without affecting milk fat. Routinary TMR particle size measurement with PSPS could be a good practice to standardize TMR particle size distribution and to maximize DMI and dairy productivity.